Permethrin resistance status and associated mechanisms in Aedes albopictus mosquitoes: implications for vector control - Janich, Ashley J., author; Kading, Rebekah C., advisor; Foy, Brian D., committee member; Dayan, Franck E., committee member (Colorado State University. Libraries, 2020)
There are major public health concerns regarding the spread of mosquito-borne diseases such as dengue, Zika, and chikungunya. The primary method to reduce the spread of these diseases is by killing the major mosquito vectors, Aedes aegypti and Aedes albopictus, with insecticides. However, with continued use of insecticides, these species have started developing resistance to the toxic effects of insecticides and higher concentrations and doses are needed to continue to effectively control these vectors. One of the insecticides that is frequently used to control these mosquitoes is permethrin, a type I pyrethroid, due to its rapid knock down effect and its low toxicity to mammals and other vertebrates. Resistance has been extensively studied in Ae. aegypti from various countries around the world. However, there are comparatively fewer studies that have examined resistance in Ae. albopictus mosquitoes, especially in the Americas. In this study, we wanted to investigate the permethrin resistance status of Ae. albopictus mosquitoes collected from Southern Mexico and Southern Texas. Additionally, we also wanted to test if permethrin resistance could be artificially selected in the laboratory over several generations. Lastly, we wanted to investigate the potential mechanisms that have been found to previously confer resistance in other mosquitoes. The two mechanisms that were investigated were knock down resistant (kdr) mutations, specifically the F1534C mutation of the voltage gated sodium channel (VGSC) gene, and the activity of metabolic enzymes that break down and detoxify insecticides. We found that there were low levels of resistance in our populations of Ae. albopictus from Mexico and Texas, with resistance ratios (RRs) ranging from 1.18 to 2.40 relative to our control strain, ATMNJ95. The results of our selected strain were unexpected. There was a gradual increase in the RR over several generations of selection, but our last selected generation had a lower RR compared to the previously selected generations. We did not find the F1534C mutation in any of our Ae. albopictus strains from Mexico. There was significantly higher cytochrome P450 activity in our permethrin-selected and non-selected strains of Ae. albopictus from Mexico compared to our control strain. The same pattern was also observed in the counterpart Ae. aegypti strains that were analyzed for comparison. Our results suggest that Ae. albopictus from the regions we sampled are still mostly susceptible to pyrethroids. However, it is possible we are observing beginning stages of resistance in this species. Alternatively, we also acknowledge the possibility that there might be ecological or historical differences between Ae. albopictus and Ae. aegypti that have resulted in different levels of resistance between the two species. It is important to continue monitoring populations of Ae. albopictus in order to prevent the development of resistance in the future.
Keywords: insecticide resistance; permethrin; Aedes albopictus